Chronic obstructive pulmonary disease risk and smoking cessation changes induced by CHRNA5-A3 and CHRNB3-A6 variation in a Chinese male population - Zhao L; Zou L-Y; Cheng B-F; Yu X-J; Zou J-H; Han W (Balkan Journal of Medical Genetics, 2019)
Most studies in the field of CHRNA5-A3 and CHRNB3-A6 have only focused on lung cancer risk; however, the associations with chronic obstructive pulmonary disease (COPD) risk and smoking cessation is less understood, particularly in the Chinese male population. In this study, samples from 823 male patients with COPD (non smokers: 416; still smoking: 407) and 435 smoking male healthy control subjects were performed with DNA extraction and single nucleotide polymorphism (SNP) genotyping. We studied three SNPS in two genes, namely rs667282 and rs3743073 in CHRNA5-A3 and rs4950 in CHRNB3-A6, and their distributions in the three groups are not statistically different (p >0.05). We grouped COPD patients according to whether they had successfully quit smoking, the CT genotype of rs667282 demonstrated association with an increased rate of successful smoking cessation compared with the TT genotype [adjusted odds ratio (OR) = 0.54, 95% confidence interval (95% CI) = 0.37-0.7, p <0.001); rs4950 AG genotypes were distinctly associated with increased rates of successful smoking cessation (adjusted OR = 0.55, 95% CI = 0.40-0.76, p <0.001). The effect is significant under the assumption of an over dominant mode of inheritance (adjusted OR = 0.58, 95% CI = 0.43 to 0.79, p <0.001). No significant difference in rs3743073 was found (p >0.05). Our findings confirmed the hypothesis that CHRNA5-A3 and CHRNB3-A6 variation are not associated with the risk of COPD. We found CHRNA5-A3 and CHRNB3-A6 were significantly associated with successful smoking cessation in smoking COPD patients.